Thomas Alva Edison : young inventor - Sabin, Louis; Ulrich, George ([Mahwah, N.J.] : Troll, 1983)
A biography, focusing on the early years, of the man whose many inventions have changed the lives of millions of people.
4.9
3-6
Keywords: Edison, Thomas A., -- 1847-1931 -- Juvenile literature; Edison, Thomas A., -- 1847-1931.; Edison, Thomas A., -- 1847-1931.; Inventors -- United States -- Biography -- Juvenile literature; Inventors; Inventors -- Biography; Inventors -- Biography